Comparison of Efficacy and Safety Between Low-Dose Ziprasidone in Combination With Sertraline and Ziprasidone Monotherapy for Treatment-Resistant Patients With Acute Exacerbation Schizophrenia: A Randomized Controlled Trial - Shi, Hui; Xu, Jing; Lang, Xiaoe; Wu, Hanjing Emily; Xiu, Mei Hong; Zhang, Xiang Yang (Frontiers in Pharmacology, 2022)
Treatment-resistant schizophrenia (TRS) is a prevalent clinical problem with heterogeneous presentations. However, the clinical trial designs for new treatments are still lacking. This study aimed to assess the efficacy of ziprasidone plus sertraline in TRS patients as compared to ziprasidone monotherapy. We conducted a 24-week, randomized, controlled, double-blinded clinical research trial. 62 treatment-resistant patients with acute exacerbation SZ were randomly allocated to receive a usual dose of ziprasidone (120-160mg/d) monotherapy (Control group) and 53 TRS inpatients were to receive a low dose of ziprasidone (60-80mg/d) in combination with sertraline (ZS group). Treatment outcomes were measured by the Positive and Negative Syndrome Scale (PANSS), the Hamilton Depression Rating Scale (HAMD), CGI-Severity (CGI-S) and Personal and Social Performance Scale (PSP) at baseline, week 4, 8, 12, and 24. Relative to control group, the patients in ZS group showed greater reductions in the following: PANSS positive symptom, negative symptom, total score, and HAMD total score. Additionally, the patients in ZS group had a greater increase in PSP total score. Notably, the reduction in HAMD was positively correlated with the reduction in PANSS total score. The reduction in CGI-S was a predictor for the improvement of psychosocial functioning in patients. Furthermore, the ZS group had a lower rate of side effects compared to the control group. Our findings suggest that a low dose of ziprasidone in combination with sertraline is an effective therapy for the clinical symptoms as compared to a usual dose of ziprasidone in the treatment-resistant patients with acute exacerbation SZ.